Strategy In Efforts To Accelerate The Reduction Of Stunting Through Posyandu In Padahurip Village, Banjarwangi District, Garut Regency - Syahril, Syahril; Fourinta, Ananda; Nurrenti, Aulya Sukma; S, Risa Azka; Murdiono, Murdiono; Topik, Alda; Nugraha, Wisnu (Indonesian Journal of Community Empowerment (IJCE), 2024)
This study aims to provide education on strategies to accelerate the reduction of stunting in Padahurip Village, Banjarwangi District, Garut Regency. The research data were collected from eight Posyandu (community health posts) in the village. The method used in this research is a qualitative approach with counseling and socialization during the Community Service (KKN) program. The results of this activity indicate an increased public understanding of the importance of stunting prevention, especially through improving nutrition for pregnant women and toddlers. The education provided was effective in raising awareness and engaging the community in efforts to reduce stunting rates in the area. The conclusion of this study is that education-based approaches through Posyandu can be an effective strategy in accelerating the reduction of stunting.